Interest Rate Pass-Through in the EMU – New Evidence from Nonlinear Cointegration Techniques for Fully Harmonized Data - Ansgar Belke; Joscha Beckmann; Florian Verheyen (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This study puts the monetary transmission process in the eurozone between 2003 and 2011 under closer scrutiny. For this purpose, we investigate the interest rate pass-through from money market to various loan rates for up to twelve countries of the European Monetary Union. Applying different cointegration techniques, we first test for a long-run relationship between loan rates and the Euro OverNight Index Average (EONIA). Based on these findings, we allow for different nonlinear patterns for shortrun dynamics of loan rates. Our investigation contributes to the literature in mainly two ways. On the one hand, we use fully harmonized data stemming from the ECB's MFI interest rate statistics. In addition, we consider smooth transition models as an extension of conventional threshold models. Our results point to considerable differences in the size of the pass-through with respect to either different loan rates or countries. In the majority of cases, the pass-through is incomplete and the dynamics of loans adjustment are different for reductions and hikes of money market rates. – – Dieser Beitrag untersucht die Zinsweitergabe der Geschäftsbanken in bis zu zwölf Ländern der Europäischen Währungsunion zwischen 2003 und 2011 für verschiedene Kreditkategorien. Mit Hilfe verschiedener Kointegrationsansätze wird zuerst geprüft, ob eine Gleichgewichtsbeziehung zwischen den Kreditzinsen und dem Tagesgeldmarktsatz des Eurosystems (EONIA) besteht. Darauf aufbauend wird die Zinsweitergabe der Geschäftsbanken auf mögliche Asymmetrien getestet. Dabei trägt diese Studie in zweierlei Hinsicht zur Forschung bei. Erstens verwenden wir einen vollkommen harmonisierten Datensatz der EZB MFI-Zinsstatistik und zweitens modellieren wir potentielle nicht-lineare Anpassungen mit sogenannten Smooth Transition-Modellen als Erweiterung zu den häufiger verwendeten Threshold-Modellen. Die Resultate deuten auf beträchtliche Unterschiede im Ausmaß der Zinsweitergabe sowohl bezüglich verschiedener Kreditkategorien als auch Länder hin. Weiterhin erscheint die Zinsweitergabe generell als unvollständig und die Anpassung an Zinssenkungen und -steigerungen erfolgt nicht-linear.
Keywords: E43; E52; F36; G21; 330; Interest rate pass-through; EMU; cointegration; ARDL bounds testing; smooth transition models